"Their last words were 'We're on strike because no-one's manning the pumps'" [Maritime Union of Australia] - Pryor, Geoff, 1944- (1994)
Ports come to a standstill when waterside workers strike over the future of the Australian National Line (ANL). Parties are keen to end the dispute quickly to avoid any legal action brought against the Maritime Union of Australia (MUA) by the employers.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 13 September 1994.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Maritime Union of Australia -- Caricatures and cartoons; Strikes and lockouts -- Australia -- Caricatures and cartoons